Ruben Dario’s Revolutionary Figure: A Performative Event at Casa de las Américas (Anclajes, 2024)
The figure and work of Rubén Darío have been the object of appropriation in Nicaragua, according to the given dominant political and ideological configurations. This paper describes and analyzes the operation performed made by Casa de las Américas, on the centennial of the birth of the poet, in 1967. In the "Encuentro con Rubén Darío" held in Varadero in February of that year and the issue of Casa de las Américas that contains the various papers given by intellectuals discussing Dario’s contributions.  The political outcome of the event was to canonize the Nicaraguan poet as anti-intellectual, together with the figures of José Martí and Simón Bolívar. The discussions that occurred among intellectuals present at the Encuentro about the figure of Darío are analyzed in this article. Finally, we describe how the appropriation of the figure and work of the poet for the revolutionary discourse occurs in Nicaragua over the next decade.
Keywords: Literature; Rubén Darío; Nicaragua; Cuba; revolution